2023
DOI: 10.3390/plants12102039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Planting Density on Sweet Potato Storage Root Formation by Regulating Carbohydrate and Lignin Metabolism

Abstract: An appropriate planting density could realize the maximum yield potential of crops, but the mechanism of sweet potato storage root formation in response to planting density is still rarely investigated. Four planting densities, namely D15, D20, D25, and D30, were set for 2-year and two-site field experiments to investigate the carbohydrate and lignin metabolism in potential storage roots and its relationship with the storage root number, yield, and commercial characteristics at the harvest period. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Sweet potato is an important tuberous root crop, and its yield depends on a change in the developmental fate of ARs into SRs [ 2 , 44 ]. The lignin biosynthesis limits sweet potato yield formation in storage roots [ 45 ]. The AP2/ERF transcription factor, IbRAP2.4, inhibited SR formation in transgenic sweet potato by comprehensively upregulating lignin biosynthesis pathway genes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sweet potato is an important tuberous root crop, and its yield depends on a change in the developmental fate of ARs into SRs [ 2 , 44 ]. The lignin biosynthesis limits sweet potato yield formation in storage roots [ 45 ]. The AP2/ERF transcription factor, IbRAP2.4, inhibited SR formation in transgenic sweet potato by comprehensively upregulating lignin biosynthesis pathway genes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lowest total root yield was from 2 plants spaced at 100cmx50cm (D ). In the study of Liang et al (2023), appropriate 3 plant spacing is critical in regulating carbohydrate and lignin metabolism affecting storage root formation. They found that a plant population of 62,520 plants ha -1 produced more storage roots.…”
Section: Yield and Yield Componentsmentioning
confidence: 99%
“…The yellow to orange-fleshed varieties contain higher levels of carotenoids an unsurpassed source of beta-, carotene a good source of vitamin A (Woolfe 1992 The establishment of an optimum population per unit area of any crop is important to achieve the crop's maximum yield (Singh Singh 2002). Liang et al & (2023) reported that a plant spacing of 80cmx20cm (62,520 plants ha ) produced -1 more storage roots than 80cmx25cm (50,025 plants ha ). This treatment also -1 stimulated the cambium cell differentiation increasing carbohydrate accumulation.…”
Section: Introductionmentioning
confidence: 99%